Atrasentan for the treatment of diabetic nephropathy. (3rd June 2017) - Egido, Jesus; Rojas-Rivera, Jorge; Mas, Sebastian; Ruiz-Ortega, Marta; Sanz, Ana Belen; Gonzalez Parra, Emilio; Gomez-Guerrero, Carmen
ABSTRACT: Introduction : Endothelin-1 (ET-1) is the most potent vasoconstrictor, and is involved in the renal regulation of salt and water homeostasis. When produced in excess in the kidney, ET-1 promotes proteinuria and tubulointerstitial injury. There is great interest in the clinical use of endothelin receptor antagonists (ERAs) in chronic kidney disease (CKD), mainly in diabetic nephropathy (DN). Areas covered : Physiopathological actions of ET-1 on the kidney. Both dual ETAR/ETB R (bosentan) or ETA R specific endothelin antagonists (avosentan and atrasentan, among others), which have progressed to early clinical development, with particular emphasis on atrasentan. Expert opinion : Different phase I and II clinical trials with ERAs in DN, mostly with atrasentan, have shown that these drugs have a marked anti-proteinuric effect on residual proteinuria when administered as add-on therapy in addition to ACEi or ARAII treatment. In the past few years, a series of randomized controlled trials investigating new approaches to DN have provided negative or inconclusive data, or even were terminated due to safety concerns or lack of efficacy. Therefore, we eagerly but cautiously await the results of the ongoing SONAR trial with atrasentan in more than 4, 000 patients including assessment of renal and cardiovascular hard-end points (estimated primary completion date, July 2018).